PENGEMBANGAN MEDIA BELAJAR DALAM PEMBELAJARAN SEJARAH AGAR MENARIK MINAT PESERTA DIDIK DALAM PEMBELAJARAN SEJARAH - AKHMAD RAKHMAN; Yeni Handayani (Jurnal Lingkar Mutu Pendidikan, 2024)
The aim of this research is to determine the application of the use of learning media in teaching history to students at SMA PKP Jakarta Islamic School. The research method used is a descriptive qualitative research method. This research technique uses observation techniques and interviews with sources. The results of this research show that there is use of learning media in history learning and it is implemented quite well